Andrographolide enhanced 5-fluorouracil-induced antitumor effect in colorectal cancer via inhibition of c-MET pathway - Su M; Qin B; Liu F; Chen Y; Zhang R (Dove Medical Press, 2017)
Meng Su,1 Baoli Qin,1 Fang Liu,2 Yuze Chen,2 Rui Zhang2 1Department of Internal Medicine, 2Department of Colorectal Surgery, Cancer Hospital of China Medical University, Liaoning Cancer Hospital and Institute, Liaoning, China Abstract: Colorectal cancer (CRC) is the third most common malignant neoplasm worldwide. 5-Fluorouracil (5-Fu) is the most important chemotherapeutic drug used for the treatment of CRC. However, resistance to 5-Fu therapies is a growing concern in CRC clinical practice recently. Andrographolide (Andro) is a main bioactive constituent of the herb Andrographis paniculata, which has various biological effects including anti-inflammation and antitumor activities. In the present study, we investigated the effects of combined Andro with 5-Fu against CRC HCT-116 cells. In vitro studies showed that Andro synergistically enhanced the anti-proliferation effect of 5-Fu on HCT-116 cells due to increased apoptotic cells. Meanwhile, results of the enzyme linked immunosorbent assay indicated that the level of phosphorylated cellular-mesenchymal to epithelial transition factor (p-MET) was decreased by the combination treatment. Further study suggested that Andro promoted the antitumor effect of 5-Fu by downregulating the level of p-MET. In conclusion, these results confirmed the synergistic antitumor activity of Andro on CRC and provide evidence for possible clinical application of Andro for enhancing the antitumor effect of 5-Fu in CRC treatment. Keywords: Andro, 5-Fu, HCT-116 cells, apoptosis, p-MET